2014
DOI: 10.11113/jt.v67.1847
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Metacognitive Skills of Secondary School Students’ Use During Problem Posing

Abstract: The purpose of our study was to explore students’ use of metacognitive skills during problem posing activities. This qualitative research explored the metacognitive skill of 21 secondary school students in a rural Anambas Indonesia while posing individually mathematical problems. Thinking-Aloud protocol was conducted during the problem posing activities. The audio recordings of Thinking-Aloud protocol for the students provided the data to address this question. Analysis of their written work and Thinking-Aloud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…A similar coding process was carried out for the strategy usage purposes of the participants. In the process of coding the purposes of the participants for using the strategies, tasks in the problem-posing steps (Polya, 1957), sub-dimensions of the Problem-Posing Skills Scale proposed by Pilten, Isik and Serin (2017), planning, monitoring, and evaluation processes of metacognitive regulation (Karnain et al, 2014), metacognitive awareness elements (Schraw & Dennison, 1994), cognitive prompts such as organization and elaboration, and metacognitive prompts such as monitoring, self-diagnosis, and planning remedial processes that encourage the use of cognitive and metacognitive strategies (Roelle et al, 2017) were used. Attention was paid to the conceptual nature of the names of the strategies and their intended use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar coding process was carried out for the strategy usage purposes of the participants. In the process of coding the purposes of the participants for using the strategies, tasks in the problem-posing steps (Polya, 1957), sub-dimensions of the Problem-Posing Skills Scale proposed by Pilten, Isik and Serin (2017), planning, monitoring, and evaluation processes of metacognitive regulation (Karnain et al, 2014), metacognitive awareness elements (Schraw & Dennison, 1994), cognitive prompts such as organization and elaboration, and metacognitive prompts such as monitoring, self-diagnosis, and planning remedial processes that encourage the use of cognitive and metacognitive strategies (Roelle et al, 2017) were used. Attention was paid to the conceptual nature of the names of the strategies and their intended use.…”
Section: Discussionmentioning
confidence: 99%
“…While the students use metacognitive strategies in this process, they are constantly engaged in how to understand information, improve a problem posing plan, formulate problems, solve problems and examine solutions (Taufik, Pagiling, Mayasari, Munfarikhatin, Natsir & Dadi, 2019). Although metacognitive strategies play an important role in problem-posing (Ghasempour et al, 2013), the literature on metacognition and problem-posing is very limited (Karnain, Bakar, Siamakani, Mohammadikia & Candra, 2014). Aydoğdu and Türnüklü (2023) 2023) investigated the predictive relations between reading strategies metacognitive awareness and problem posing skills of seventh grade students.…”
Section: Strategies Used In the Problem-posing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Problem-posing activities can promote both students' metacognitive skills (Karnain et al, 2014 ) and their mathematical dispositions (Silver, 1994 ; Wang et al, 2021 ). Specifically, suppose students are given a mathematical problem, they are required to generate some similar problems.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Studies have indicated that metacognition, together with intrinsic characteristics (such as motivation, control, willingness and reinforcement), are important factors for students to pose problems. For example, Karnain et al (2014) emphasised that metacognition is a critical element for problem posing. The authors claim that students with improved metacognitive skills will also have developed problem-posing skills.…”
Section: Problem Posingmentioning
confidence: 99%